PENGARUH CUSTOMER EXPERIENCE DAN E-WOM TERHADAP MINAT PEMBELIAN ULANG PELANGGAN MIE KOBER JEMBER - Damayanti, Alfia; Handini, Yuslinda Dwi; Wahyudi, Edy (Jurnal Administrasi Bisnis, 2024)
This study aims to determine the effect of customer experience and electronic word of mouth on customer repurchase intentions of Mie Kober Jember. The type of research used is explanatory research with a quantitative approach. The sample used was 120 respondents using a purposive sampling technique with the condition that the respondent had made a direct purchase or dined in at Mie Kober Jember, Karimata Branch twice or more. The results showed that the customer experience variable had a significant effect on customer repurchase intention of Mie Kober Jember. Meanwhile, electronic word of mouth variable has no significant effect on customer repurchase intention of Mie Kober Jember caused by the low level of discussion between customers on social media. Even so, together the variables of customer experience and electronic word of mouth have a significant effect on the repurchase intention of Mie Kober Jember customers.